An improved topology of digitally-controlled single-phase single-stage high DC voltage converter - Mekhilef, Saad; Omar, A.M.; Muhammad, K.S. (2006)
This paper presents An improved topology of digitally-controlled single-phase single-stage high dc voltage converter where CPLD is used to develop the PWM switching pattern which will be discussed in detail. The proposed system utilizes a single-phase AC input supply. The power switching devices in the controlled bridge are controlled by the multiple-pulse Pulse Width Modulation (PWM) switching technique to minimize the low order harmonics present on the AC side of the converter. A low pass Alter is incorporated in the circuit to Alter out unwanted harmonics and provide a sinusoidal AC supply current. A high frequency transformer with 1:1 ratio is used in the design to provide galvanic isolation for better circuit performance and protection. The optimum operation of transformer core in four quadrant of B-H curve is also considered in the proposed converter topology. A laboratory prototype of the converter is developed and tested. Experimental results are compared with the simulation results to illustrate the effectiveness of the proposed technique.